Evaluation of losses in a bidirectional wireless power transfer system for electric vehicles - Triviño-Cabrera, Alicia; Cabello-González, José Manuel; Aguado-Sánchez, José Antonio (My University, 2017)
Inductively power transfer systems are becoming increasingly popular in modern applications like electric vehicles. In order to make this technology attractive, its transfer efficiency must be considerably high. Most works in the literature define the efficiency of the wireless charger as the one associated to the inverter, the coupled coils and the compensation networks. Therefore, they usually omit the study of the losses occurring in other parts of the system such as in the secondary rectifier. This paper evaluates the losses in a complete wireless charger, built and designed to provide V2G functionalities. The experimental evaluation based on the waveform analysis is contrasted with a theoretical model, which relies on the non-idealities of the components. The evaluation reveals that measurement error greatly impact on the power losses derived by the two approaches
Keywords: Vehículos eléctricos; Electric vehicle; Wireless charger